A novel food-based foam as oral contrast agent with negative Hounsfield units for demarcation of small bowel loops on abdominal CT: tolerability and bowel distension in 25 volunteers. (December 2021) - Leander, Peter; Adnerhill, Ingvar; Böök, Olof; Casal-Dujat, Lucia; Stathis, Georgios; Fork, Thomas
Background: Diseases of the bowel are not always displayed on conventional abdominal computed tomography (CT). The studied oral contrast agent aims to improve this. Purpose: To investigate whether the use of a novel oral contrast for abdominal CT enables the same diagnostic advantages as seen in magnetic resonance imaging (MRI). Material and Methods: Twenty-five consented volunteers drank up to 1400 mL of a stable, drinkable foam. Comments on acceptance and side effects were noted immediately and 24 h later. Foam palatability was documented through interviews, and distribution in the small bowel by Hounsfield units from the CT software. The CT results were compared with age- and sex-matched controls, pretreated according to routine. A non-enhanced abdominal CT protocol of lowest possible radiation dose was used. External referees evaluated all data obtained. Results: Foam was considered odd to swallow, and fullness was reported by all volunteers after 950 mL. Five had difficulties in drinking the last 320 mL and two abstained from it. All adverse symptoms were mild. The distribution in the small bowel was on par with standard agents. Foam density revealed stability with intraluminal values of around –550 HU from stomach to terminal ileum, satisfying the requirement of a great bowel lumen-to-wall contrast. External reviewers re-evaluated all our data, and one predicted the foam to offer a potential for improved diagnostics. Conclusion: A CT true-negative bowel filling agent was formulated, with high acceptance, few side effects, and a potential to mimic T1-weighted MRI images.